2011
DOI: 10.1353/asi.2011.0008
|View full text |Cite
|
Sign up to set email alerts
|

Mobility, Economic Strategies, and Social Networks: Investigating Movement in the Mewar Plain of Rajasthan

Abstract: Mobility is an important part of life for those who practice a variety of economic strategies including foraging, pastoralism, craft production, service provision, and performance. Studies of mobility can contribute to broader understandings of social networks, community formation, and social identity in South Asia during the first few millennia b.c ., a time of early social complexity. Previous ethnographic and archaeological research in the region shows a range of ways that mobile people form relationships w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The experiences presented here come from four separate research projects and span our graduate research and early careers (Raczek 2011;Sugandhi 2014;Sugandhi et al 2010). While we did not explicitly design all of these projects to be participatory or devoted to heritage work, they nevertheless included substantial community interactions that highlighted the importance of language and communication as critical to building trust among participants, establishing our field identities, and undertaking delicate conversations about heritage.…”
Section: Communicating In North and South Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…The experiences presented here come from four separate research projects and span our graduate research and early careers (Raczek 2011;Sugandhi 2014;Sugandhi et al 2010). While we did not explicitly design all of these projects to be participatory or devoted to heritage work, they nevertheless included substantial community interactions that highlighted the importance of language and communication as critical to building trust among participants, establishing our field identities, and undertaking delicate conversations about heritage.…”
Section: Communicating In North and South Indiamentioning
confidence: 99%
“…That capacity for engagement also varied a great deal between north and south India. Raczek's (2011) dissertation included a survey to identify stone raw material sources on the Mewar Plain in Rajasthan, North India. As she undertook this work, she recruited a small local crew and trained them in archaeological methods and general Indian prehistory.…”
Section: Communicating In North and South Indiamentioning
confidence: 99%
“…Emphasis has been given on cores since blade cores have been considered formal technologies (Raczek 2007). It has also been suggested that blade cores are portable, efficient and highly suitable for the condition of mobility (Parry 1994, Raczek 2011.…”
Section: Coresmentioning
confidence: 99%